Pengaruh Literasi Keuangan, Inklusi Keuangan, dan Financial Technology terhadap Kinerja UMKM - Ola, Kiki Putri; Utami, Endang Sri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
With a strong emphasis on micro businesses in the culinary industry in Depok District, this study seeks to examine in depth the impact of financial literacy, financial inclusion, and financial technology on the performance of MSMEs. The importance of improving financial knowledge, accessibility to formal financial services, and the use of financial technology for micro businesses, which often face limitations in resources, capital, and information, forms the main basis of this study. In this study, questionnaires serve as the main instrument, which has been validated and tested for reliability to ensure the quality and accuracy of data using a quantitative approach. The research population consisted of 9,246 MSMEs operating in Depok District, and the sample size was selected using the Slovin formula, resulting in 100 respondents. Multiple linear regression and partial t-tests were used in data analysis to evaluate the impact of each independent variable on MSME performance at a significance level of 0.05. Based on the analysis results, financial literacy has a significant and positive effect on MSME performance, as evidenced by a regression coefficient value of 0.152, a t-value of 2.296, and a p-value of 0.024. Financial inclusion has a positive and significant effect on MSME performance, as evidenced by a regression coefficient value of 0.100, a t-value of 2.164, and a p-value of 0.033. On the other hand, financial technology also has a significant and positive effect on MSME performance, as evidenced by a regression coefficient value of 0.136, a t-value of 2.269, and a p-value of 0.025.